Tanggung Jawab Hukum atas Pelanggaran Penggunaan Data Medis dalam Penelitian Kesehatan Tanpa Persetujuan Pasien - DWI ARMAN PRASETYA (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the legal framework and legal liability for the use of patients' medical data in health research without patient consent. The findings show that medical data constitute specific personal data under Article 4(2) of Law Number 27 of 2022 on Personal Data Protection, requiring informed consent or another lawful basis for processing. Unauthorized use of medical data may result in administrative, civil and criminal liability under Article 67 of the Personal Data Protection Law and Article 30 in conjunction with Article 46 of the Electronic Information and Transactions Law when involving unauthorized access to electronic systems. Strengthening regulatory guidelines, institutional oversight and informed consent procedures is essential to protect patients' medical data.